The interconnected work of a preschool educational organization with a family, mahalla in order to develop children in order to prepare them for school (Eurasian Journal of Learning and Academic Teaching, 2023)
This article is devoted to the relationship between the work of a preschool educational organization, family and mahalla in order to enroll children in a preschool educational organization to prepare them for school. About the variety of forms of work with parents of preschool children.